Modeling and design of solar energy systems including solar economics - Kalogirou, Soteris A. (My University, 2012)
The design of a solar energy system is a complex problem. As such it includes both predictable and unpredictable parameters. The former are related to performance characteristics of collectors and other components and the latter mainly concern weather data such as solar radiation, ambient temperature, wind speed and direction, and other less important environmental parameters. In this chapter, a simple design method and a simple modeling technique are presented as well as an overview of TRNSYS which is the simulation program suitable for modeling active solar heating systems. The design method presented is the f-chart. This is based on the correlation of the results of a large number of TRNSYS simulations in terms of easily calculated dimensionless variables. The f-chart can be used to model active liquid and air systems and active systems used to provide only hot water. These are explained in this chapter together with a modification to use the method for estimating the performance of thermosiphon solar water heating systems, which constitute the great majority of solar water heating systems. This is followed by simple models of solar energy systems suitable for analysis of the systems on hourly basis. In recent years, because of the increase of computational speed of personal computers, annual simulations have replaced design methods. Design methods however, are much faster; therefore they are still useful in early design studies. For more detailed results modeling and simulation is used. The software programs described briefly in this chapter include the F-chart and TRNSYS. Finally, the way to perform economic analysis of solar energy systems is presented and in particular the life cycle analysis. It is also indicated how to optimize a solar energy system using the economic analysis.
Keywords: F-chart method; Liquid solar energy systems; Air solar energy systems; Service water systems; Thermosiphon systems; Modeling; Simulations; Simple models